Effect of Killing Method and Post-Mortem Duration on the Freshness Quality of Tilapia Fish (Oreochromis Mossambicus) Fillet - Owen, Oliver; Widia, I Wayan; Kinasih, Mentari (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
Tilapia fish filet is one of the protein-rich foods needed by the body. The freshness quality of the tilapia fish filet is affected by the quality of the raw materials and the method of killing the fish. This study aimed to determine the effect of the lethal technique and the length of post-mortem time on the freshness of tilapia fish (Oreochromis mossambicus) filets. This study used a factorial-CRD trial (Completely Randomized Design) for two factors. The first factor is how to kill the fish (floating death, cold temperature, and ikejime technique). The second factor was the length of post-mortem time (0, 2, 4, 6, 8, 10, 12, and 14 hours). Each treatment was repeated by 2 times so that 48 samples were obtained from 24 treatment combinations. The observed parameters are the rigor index, organoleptic freshness, pH, and protein content. Observational data were processed by Analysis of Variance (ANOVA), Duncan test, and Kruskal-Wallis test. The results of this study indicate that the method of shutting down and the length of time post-mortem significantly affect several parameters of the freshness quality of tilapia fish fillets. The best combination of treatment is lethal with the ikejime technique with a post-mortem time of 0 hours which has a pH of 6.94, protein content of 26.65% and fish meat organoleptic score of 8.80, and fish meat texture score of 8.95.